Program Vinglish Melalui Flipbook Based E Module dan English Ecological Spot untuk Meningkatkan English Literacy - Ima Isnaini Taufiqur Rohmah; M. Zainudin; Fitri Nurdianingsih (Jurnal Pendidikan Edutama, 2022)
Abstract:  Vinglish (Village of English) is a partnership program design between lecturers and students of IKIP PGRI Bojonegoro with the Village Government that focuses on scientific research in rural community education in order to accelerate English Literacy of village human resources. The purpose of this research is to describe the implementation of VINGLISH with the help of Flip Book Based E-Module and English Ecological Spot to improve English Literacy of villagers. This research will apply a case study qualitative approach. The results showed that there was an increase of 27% in English literacy of villagers who were safe targeted at village children and village officials. This study recommends a more in-depth study of the effectiveness of the VINGLISH (Village of English) program which is viewed from villagers autonomous learning. Abstrak: inglish (Village of English) merupakan sebuah rancangan program kemitraan antara dosen dan mahasiswa IKIP PGRI Bojonegoro bersama Pemerintah Desa yang berfokus pada Riset keilmuan pendidikan masyarakat desa dalam rangka akselerasi English Literacy sumberdaya manusia desa. Tujuan dari penelitian ini adalah mendeskripsikan implementasi VINGLISH dengan bantuan Flip Book Based E-Module dan English Ecological Spot untuk meningkatkan English Literacy warga desa. Penelitian ini akan menerapkan pendekatan kualitatif studi kasus. Hasil penelitian menunjukkan bahwa terdapat keniakan sejumlah 27% English literacy warga desa yang aman disasarkan pada anak-anak desa dan perangat desa. Penelitianini merekomendsikan untuk kajian lebih mendalam tentang efektivitas program VINGLISH (Village of English) yang ditinjau autonomous learning